Influence of the form anysotropy of silicon nanostructures on their optical properties - Sekerbayev, K. S.; Taurbayev, T. I.; Timoshenko, V. Yu. (Recent Contributions to Physics, 2013)
Within a framework of approaching the effective media and Drude-Lorenz Model, the calculations of the optical characteristics, which include the refraction index and absorbability in the spectral region below the end of band-to band absorption, assemblies of silicon nano crystals with various form and space-filling factor, have been done. The expressions for frequency profiles of components of the complex dielectric constant of the system of the oriented ellipsoids, wires and layers, have been achieved, and the conditions for reaching the maximal optical anisotropy with minimal optical losses have been found. It follows from the calculations that maximal optical anisotropy is achieved for the system of parallel planes, and equals to 1 when having porosity equal to 0.3. The system of planes acts as the negative uniaxial crystal, and the wires – as positive uniaxial crystal. The maximal optical anisotropy for the wires is equal to 0.65 when having porosity equal to 0.6. Absorbability of medium strongly depends on emission frequency and achieves its maximum when having frequencies about 200 cm-1. Increase of charge carrier concentration can result in significant increase of birefringence and absorption. Applicability of the achieved results for describing the optical properties of porosilicon and other silicon nanostructures is discussed.